2022
DOI: 10.1111/os.13398
|View full text |Cite
|
Sign up to set email alerts
|

Zero‐Profile Implant System for Treatment of Dysphagia Caused by Noncontiguous Anterior Cervical Osteophytes—A Case Report with Literature Review

Abstract: Background: Esophageal cervical spondylosis is a rare type of cervical spondylosis which causes dysphagia. Surgical osteophyte resection is taken when conservative treatment does not respond. However, few reports on its operation and postoperative follow-up. We first present a case showing how the Zero-Profile implant system is utilized to treat dysphagia caused by noncontiguous anterior cervical osteophytes.Case Presentation: A patient with progressive dysphagia was referred to our department. Imaging examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…When the osteophytes in the vertebral column are examined according to the regions, the incidence of osteophytes in the cervical vertebrae in individuals over 65 years of age is 80-85% (Peng, Liu, Hong, & Meng, 2022). In a study conducted in Japan, the presence of osteophytes was examined in terms of age and it was shown that the frequency of osteophytes increased with age (Chiba et al, 2022;Watanabe & Terazawa, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…When the osteophytes in the vertebral column are examined according to the regions, the incidence of osteophytes in the cervical vertebrae in individuals over 65 years of age is 80-85% (Peng, Liu, Hong, & Meng, 2022). In a study conducted in Japan, the presence of osteophytes was examined in terms of age and it was shown that the frequency of osteophytes increased with age (Chiba et al, 2022;Watanabe & Terazawa, 2006).…”
Section: Discussionmentioning
confidence: 99%